Dealer process efficiency, revenue generation and customer satisfaction utilizing gamification models: An empirical study- With special emphasis on Skoda Auto Volkswagen India Private Limited - Deshmukh, Dr Renuka; Pasumurti, Dr Subbarao; Tharkude, Dr Dhanashri; Jadhav, Mr. Rajsingh; Mool, Ms. Meenal (The journal of contemporary issues in business and government, 2023)
Purpose: The purpose of the study is to investigate the interrelationship and the impact of Utilization, Customer Satisfaction and Revenue in company authorized service dealership and to examine the relationship between these factors and demographics. Design/Methodology: For this research, a structured questionnaire survey is used to collect data from service managers and other dealership employees such as floor manager, customer relations manager, inventory manager. Analysis of data is done using a multivariate technique like relative importance index and factor analysis. Findings: The most significant top five attributes/variable of the study are; interrelationship between the three key performance areas of automobile dealership i.e. Utilization, Customer Satisfaction and Revenue and how one KPA (key performance area) impacts the others. To establish an equilibrium between KPA’s to achieve profit maximization. Furthermore, the factor analysis produced 7 constructs such as; tangible, reliability, empathy, experience, courtesy & responsiveness feedback and productivity explained a variance of 65.5%. Practical Implications- This research study will generally help the service managers to increase efficiency and profitability of the dealerships. It will contribute to improve the operational as well as the managerial perspective via a gamification-based approach. Limitations: The study has been conducted on the data acquired from the service managers and training department of the dealerships and the company respectively and the findings may not be generalized for all the dealerships because of socio-economic and demographic differences. A key limitation of this study is the sampling frame. Some respondents do not share their dealership data for their data integrity purposes. The information provided by the respondents may not be considered accurate. The primary data collected is from Pune city. Future studies should replicate this study in different contexts.